Pengaruh Cash Ratio dan Earning Per Share Terhadap Dividend Pay Out Ratio pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Peri Setiawan; Suradi; Aprilianto Amir (Business Perspective Journal, 2023)
The capital market is one of the ways chosen by the company in meeting the needs of additional company funds to develop the company's operations to survive in the global economy. Investors invest their capital in shares in a company with the main objective of obtaining a return on investment in the form of dividends and capital gains. The purpose of this study is to analyze the effect of Cash Ratio and Earnings Per Share on Dividend Payout Ratio in manufacturing companies listed on the Indonesia Stock Exchange. The data used are secondary data that is produced from other existing sources, for example research must go through others or search through documents, journals or books (name, year, page,). This research is a quantitative study with a descriptive approach. Samples of this study using panel data, were taken as many as 8 manufacturing companies that were in accordance with predetermined criteria with the research period 2016 - 2020. The study used the software of SPSS 2.0 and the results ere Cash Ratio effects the Dividend Payout Ratio based on the results of calculations and analysis can be calculated t-value = 6.255 with a sig. Value = 0.000., This significant value <0.05,. Earning Per Share has a significant effect on the Dividend Payout Ratio based on the results of calculations and analysis obtained calculated t-value = 3.837 with a sig. value. = 0.001, sig. value = 0.001 < 0.05, Cash ratio and Earning Per Share have a significant effect on the Dividend Payout Ratio based on the calculation and analysis results obtained value t-calculate = 69.818 the value of sig. = 0.000 because the value of sig. < 0.05 the result of the coefficient of being amended adjust R2 obtained 0.951, means that this study contributed 95.1% while 4.9% was determined by other factors outside this study, this hall showed that the available data had qualified for the use of the panel data regression model. From the results of the analysis, it shows that the Cash Ratio, and Earning Per Share effect to the Dividen Payout Ratio. Keywords: cash ratio, earning per share, and dividend payout ratio, capital market